Soper, Harriet. 2024. The Life Course in Old English Poetry. Cambridge: Cambridge University Press. Pp. i + 267. ISBN 9781009315111. - Brooks, Britton Elliott (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Soper, Harriet. 2024. The Life Course in Old English Poetry. Cambridge: Cambridge University Press. Pp. i + 267. ISBN 9781009315111.